2023
DOI: 10.3389/fimmu.2023.1117630
|View full text |Cite
|
Sign up to set email alerts
|

An updated review of the immunological mechanisms of keloid scars

Abstract: Keloid is a type of disfiguring pathological scarring unique to human skin. The disorder is characterized by excessive collagen deposition. Immune cell infiltration is a hallmark of both normal and pathological tissue repair. However, the immunopathological mechanisms of keloid remain unclear. Recent studies have uncovered the pivotal role of both innate and adaptive immunity in modulating the aberrant behavior of keloid fibroblasts. Several novel therapeutics attempting to restore regulation of the immune mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 245 publications
0
4
0
Order By: Relevance
“…Overproduction of ECM is closely related to prolonged inflammation in keloid pathogenesis. Keloid formation is driven by multiple cytokines, growth factors, and transcription factors [ 2 , 35 ]. The study by Nangole et al [ 36 ] revealed that the high expression of proinflammatory cytokines in keloid impacts the sensitivity and increases the production of collagen on keloid fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Overproduction of ECM is closely related to prolonged inflammation in keloid pathogenesis. Keloid formation is driven by multiple cytokines, growth factors, and transcription factors [ 2 , 35 ]. The study by Nangole et al [ 36 ] revealed that the high expression of proinflammatory cytokines in keloid impacts the sensitivity and increases the production of collagen on keloid fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Keloid development involves a local infiltration of inflammatory cells including mast cells [7]. Cocultured HMC-1 stimulated the collagen 1 expression of KFs, and it was attenuated by a blockade of PI3K, mTOR, and p38 MAPK [107].…”
Section: The Potential Of Natural Product-based Therapy and Future Tasksmentioning
confidence: 99%
“…Keloid is a type of scarring that occurs due to abnormally high cell proliferation and the excessive accumulation of ECM during the healing process of a skin injury [7,8]. Keloids are similar to hypertrophic scars in that they involve the proliferation of dermal fibroblasts and accumulation of ECM, but keloids differ in that they grow beyond the boundaries of the initial injury [9].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that exosomes isolated from human adipose MSCs can reduce the proliferation of scar fibroblasts and collagen synthesis by inhibiting the TGF-β/Smad signaling pathway and improve scar formation in burn wounds [49]. Keloid fibroblasts are a specific type of fibroblasts that appear during the wound healing process; they are highly proliferative and secretory but lack the ability to degrade and remodel the extracellular matrix, leading to the excessive deposition of extracellular matrix and fibrosis of the tissue [50]. The TGF-β/Smad signaling pathway is a signal transduction pathway involved in cell proliferation and differentiation, and plays an important role in the regulation of scar formation [51].…”
Section: The Wound Healing-promoting Mechanisms Of Mesenchymal Stem C...mentioning
confidence: 99%